Mammalian Overlapping Genes: The Comparative Perspective - Veeramachaneni, Vamsi; Makalowski, Wojciech; Galdzicki, Michal; Sood, Raman; Makalowska, Izabela (Genome Research, 2004)
It is believed that 3.2 billion bp of the human genome harbor ∼35,000 protein-coding genes. On average, one could expect one gene per 300,000 nucleotides (nt). Although the distribution of the genes in the human genome is not random,it is rather surprising that a large number of genes overlap in the mammalian genomes. Thousands of overlapping genes were recently identified in the human and mouse genomes. However,the origin and evolution of overlapping genes are still unknown. We identified 1316 pairs of overlapping genes in humans and mice and studied their evolutionary patterns. It appears that these genes do not demonstrate greater than usual conservation. Studies of the gene structure and overlap pattern showed that only a small fraction of analyzed genes preserved exactly the same pattern in both organisms.